Comparative optimization of combinatorial CRISPR screens - Ruitong Li (Nature Communications, 2022)
Combinatorial CRISPR screens can be utilized to identify genetic interactions and functional redundancies of multiple genes. Here, the authors benchmark ten digenic CRISPR technologies and identify novel Cas9 tracrRNA combinations that show superior performance.